2000
DOI: 10.1086/315332
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin, an Elastase Inhibitor, Inhibits the Increased mRNA Expression of Prostaglandin H2Synthase–Type 2 in Kawasaki Disease

Abstract: Kawasaki disease is an inflammatory disease of unknown cause that causes panvasculitis, including coronary arteritis. Polymorphonucleocytosis in the early stage of the illness suggests the implication of neutrophils in the pathogenesis of the disease. In the acute phase of Kawasaki disease, mRNA expression of prostaglandin H2 synthase (PHS)-2, as determined by reverse transcription-polymerase chain reaction, was markedly enhanced, and thromboxane A2 (TXA2)-synthesizing activity was increased in polymorphonucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 32 publications
(39 reference statements)
1
45
0
Order By: Relevance
“…Although we could not demonstrate the infiltration of neutrophils in the coronary artery wall, a previous pathologic study confirmed (6). Recently, treatment with a neutrophil-elastase inhibitor, ulinastatin, was reported to be a potential adjunct to ␥-globulin therapy in acute KD (22). iNOS expression in neutrophils may reflect their activation and enhanced function in the early phase of acute KD, as reported previously (23).…”
Section: Discussionsupporting
confidence: 65%
“…Although we could not demonstrate the infiltration of neutrophils in the coronary artery wall, a previous pathologic study confirmed (6). Recently, treatment with a neutrophil-elastase inhibitor, ulinastatin, was reported to be a potential adjunct to ␥-globulin therapy in acute KD (22). iNOS expression in neutrophils may reflect their activation and enhanced function in the early phase of acute KD, as reported previously (23).…”
Section: Discussionsupporting
confidence: 65%
“…This 67 000-Dalton glycoprotein inhibits neutrophil elastase as well as prostaglandin H2 synthase at the messenger RNA level. 175 Ulinastatin has been proposed as useful in IVIG-refractory patients, 175 but its effectiveness is unproven, and additional experience with this agent is necessary before it can be recommended (evidence level C).…”
Section: Other Treatmentsmentioning
confidence: 99%
“…This 67 000-Da glycoprotein inhibits neutrophil elastase as well as prostaglandin H2 synthase at the messenger RNA level. 175 Ulinastatin has been proposed as useful in IVIG-refractory patients, 175 but its effectiveness is unproven and additional experience with this agent is necessary before it can be recommended (evidence level C).…”
Section: Other Treatmentsmentioning
confidence: 99%